Investigation of robotic welding process by using RobotStudio™5.10 and ABB robot / Shahfuan Hanif Ahmad Hamidi - Ahmad Hamidi, Shahfuan Hanif (2009)
This project discussed about the investigation of robotic welding using RobotStudio™5.10 Software and ABB Robot. In this project there are two approaches that have been taken, simulation and execution. In simulation, there are several steps need to be carried out. Those are CAD modeling, layout arrangement, and rapid programming which are available on RobotStudio™5.10 Software. The author makes some study cases on this software on basic understanding for the readers. The study cases are including simple geometry for generating rapid program, I/O programming where in creating signal with other devices and advanced rapid programming by creating new movement function. In execution approach, the author executes a rapid programming directly to ABB robot. These activities required some preparation before, during, and after execution. Therefore, the author used example of ship panel structure to adapt all the preparation that need to be carried out. This example is documented together with the suitable welding parameter. In conclusion, by reading this book, readers should have general ideas of basic fundamental in applying in simulation and execution of robotic. They also know about the advantages of the software and the robot itself.